2017
DOI: 10.1159/000480010
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Variability in Macaques and Langurs of the Western Ghats, India

Abstract: Studies that compare differences in the behavioural variability across species and genera are rare among south Asian primates. Such studies are important for understanding within-group feeding competition in primates as interindividual difference in frequency of behaviour is a good indicator of feeding competition. We compared the variability in individual activities of lion-tailed macaques, bonnet macaques, Nilgiri langurs, and black-footed grey langurs. Both macaque species showed variability in their activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The reduced likelihood of natural cross species transmission is important as it increases the probability of hostvirus co-evolution. Further, for example while lion-tailed and bonnet macaques ranges overlap, different living strategies (frugivorous and arboreal vs generalist in human dominated environments respectively) [58,59] between these animals make cross transmission unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced likelihood of natural cross species transmission is important as it increases the probability of hostvirus co-evolution. Further, for example while lion-tailed and bonnet macaques ranges overlap, different living strategies (frugivorous and arboreal vs generalist in human dominated environments respectively) [58,59] between these animals make cross transmission unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…(Kavana 2015) and Joseph J. Erinjery (Erinjery 2016) (https://www.researchgate.net/profile/Joseph_J_ J TT Erinjery) studied individual differences indicating behavioral variability in macaques (Bonnet and Liontailed) and langurs (Nilgiri and Hanuman), respectively. Behavioral variability was higher in macaques than in langurs (Erinjery et al 2017b). The ideal gas model approach showed that primates in the Western Ghats do not form active associations with each other .…”
Section: University Of Mysore Mysurumentioning
confidence: 91%
“…The reduced likelihood of natural cross species transmission is important as it increases the probability of host-virus co-evolution. Further, for example while Lion-tailed and Bonnet macaques ranges overlap, different living strategies (frugivorous and arboreal vs generalist in human dominated environments respectively) [60,61] between these animals make cross transmission unlikely.…”
Section: Host-virus Co-speciationmentioning
confidence: 99%